Gallbladder cholelithiasis and inflamation Organic stenosis of the papila, a surgical myth? - Delgado, Bolívar (Cirugía del Uruguay, 1987)
The associallon between gallbladder cholelith.iasis and inflamatory organic stenosis of the papilla, as has been referred by many authors with variable rate, couldn't been demonstrated in a serie of 300 cholecystectomies with intraoperatory radiomanometric control. Facts are analysed and the author expresses his doubts about its actual existence